Nickel-copper-boron nitride powder and method for producing the same

CN117753961BActive Publication Date: 2026-10-20LIAONING SILICATE RES INST +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311796998.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-26
Publication Date
2026-10-20
Estimated Expiration
2043-12-26

AI Technical Summary

Technical Problem

该方法操作简单方便,得到的粉体包覆性好;缺点是使用的还原性气体安全性较差,且得到的粉体团聚性严重

Benefits of technology

[0033]本发明提供镍铜氮化硼粉体的制备方法具有如下优点:利用流体法中高速气流促进液流快速蒸发的特点,可以使镍铜氮化硼粉体的包覆形貌明显提高,同时也完成了金属相的掺杂,从而明显提高粉体的性能;通过对气相流的控制,能够精准地控制金属相的配比,可根据需要进行调节,铜元素的引入进一步改善涂层的强度和硬度、提高涂层的耐腐蚀、耐氧化等性能;采用低温还原烧结的工艺,通过低温下的碳还原作用,无需采用还原气体并配合高温进行还原,降低了生产成本,同时也保证了粉体的纯度;采用市销原料,工艺设备简单,无需保护气体、降低了产业化的门槛,生产成本低,可明显的提高生产效率,满足了大批量生产的要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117753961B_ABST
    Figure CN117753961B_ABST
Patent Text Reader

Abstract

The application discloses a kind of nickel copper boron nitride powder and preparation method thereof, the nickel copper boron nitride powder is prepared using fluid method, using conventional nickel powder, copper powder, boron nitride powder and additive, after fluid preparation, jet mixing, low-temperature reduction sintering, screening process, the nickel copper boron nitride powder with uniform composition, controllable, high relative density, good fluidity, wide particle size range is prepared, the nickel copper boron nitride powder can meet the use of various spraying equipment, can prepare wear-resistant coating, sealing coating, lubricating coating, improve the service life of relevant product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nickel-copper boron nitride powder preparation, and in particular provides a nickel-copper boron nitride powder and its preparation method. Background Technology

[0002] Hexagonal boron nitride crystals exhibit a layered stacked structure with weak interlayer bonding, allowing for easy crystal facet slippage and making them an excellent self-lubricating material with a low coefficient of friction. Combined with its superior mechanical properties, thermal conductivity, insulation, thermal stability, and chemical stability, it has broad market application prospects.

[0003] Metallic materials such as nickel, copper, and aluminum have excellent ductility, high electrical conductivity, and high thermal conductivity, and are widely used in many industries such as power electronics, energy petrochemicals, and machinery metallurgy. However, their applications are limited by their relatively low mechanical properties. Combining these metallic materials with boron nitride can effectively improve this situation.

[0004] Nickel-boron nitride composites can improve the strength and hardness of materials; copper-boron nitride composites can improve the high-temperature oxidation resistance and thermal conductivity of materials; aluminum-boron nitride composites can be used as high-temperature wearable sealing coating powder materials to improve the working efficiency of aero engines, reduce friction between blades and casings and between grates and sealing rings, and protect mechanical components.

[0005] Currently, there are several methods for preparing nickel boron nitride composite powder: (1) Chemical plating: First, the boron nitride powder is roughened, sensitized, and activated; then, nickel salt plating solution, dispersion solution, and reduction solution are prepared; the three are put into a beaker in sequence, stirred slowly, and centrifuged after the reaction is completed, washed with water and vacuum dried to obtain nickel-coated boron nitride powder. The advantage of chemical plating is that it can uniformly plate metallic nickel onto the surface of boron nitride; the disadvantage is that it is expensive, complicated to operate, and costly. (2) Hydrothermal hydrogen reduction: Nickel salt is prepared into a solution according to a certain proportion, mixed with the pretreated boron nitride powder, and then placed in a high-pressure reactor. A catalyst is added, the high-pressure reactor is sealed, and stirring is started. After the temperature rises, hydrogen gas is introduced. During the reaction, attention should be paid to timely replenishment of reducing gas to maintain constant pressure. After the reaction is completed, the temperature is lowered, the gas is released, and the reactor is unloaded. The slurry is taken out for solid-liquid separation, washing, and drying. The advantages of hydrothermal hydrogen reduction are fast reaction speed, controllable reaction scale, and high raw material utilization rate; the disadvantages are high equipment requirements, high cost, and poor safety. (3) Mechanical method: Nickel powder, boron nitride powder, and binder are mixed and stirred in a ball mill. The wet material is then sieved and dried. This method is simple to operate, but the raw materials are difficult to mix evenly, and the powder agglomeration is severe. (4) Solid-state reaction method: Metallic nickel powder and boron nitride powder are mixed evenly in a certain proportion and calcined at high temperature in a reducing atmosphere of hydrogen or carbon monoxide. Ultrafine coated powder is directly obtained through solid-state reaction. This method is simple and convenient to operate, and the obtained powder has good coating properties; the disadvantage is that the reducing gas used has poor safety, and the obtained powder has severe agglomeration.

[0006] Therefore, how to improve the corrosion resistance and oxidation resistance of nickel-plated boron nitride from the aspects of raw materials and processes, and thus significantly improve the strength and hardness of the sealing coating, has become an urgent problem to be solved. Summary of the Invention

[0007] Therefore, the purpose of this invention is to provide a nickel-copper boron nitride powder and its preparation method, so as to solve the problems existing in the prior art.

[0008] This invention provides a nickel-copper boron nitride powder, comprising, by weight: copper: 10-30%, boron nitride: 9-20%, carbon: 0-10%, silicon ≤5%, and the balance being nickel, wherein the loose packing density of the nickel-copper boron nitride powder is 1-2 g / cm³. 3 The fluidity is ≤120s / 50g, and the particle size is between -100 mesh and +400 mesh. The nickel-copper-boron nitride powder component has a dispersed polymer structure.

[0009] This invention also provides a method for preparing nickel-copper boron nitride powder, comprising the following steps:

[0010] 1) Powder selection

[0011] Select nickel powder, copper powder, boron nitride powder, and graphite powder with a purity higher than 99.99%, and the powder particle size is in the range of 2-150μm;

[0012] 2) Additive selection

[0013] Water glass or silica sol is selected as the binder and prepared as an aqueous solution with a concentration of 1-5%.

[0014] 3) Preparation of airflow powder

[0015] Nickel powder and copper powder are added to a mixer in a weight ratio of 4 / 3 to 7 / 1 and mixed to obtain airflow powder.

[0016] 4) Preparation of liquid-powder slurry

[0017] Graphite powder and boron nitride powder were added to a ball mill at a weight ratio of 0-1 / 1 and mixed to obtain liquid flow powder.

[0018] The liquid flow powder is mixed with a liquid flow solvent and a binder to obtain a liquid flow powder slurry, wherein the liquid flow solvent is water or an organic solvent;

[0019] 5) Fluid jet mixing

[0020] High-pressure gas is used to spray air-flow powder and liquid-flow powder slurry, wherein the weight ratio of air-flow powder to liquid-flow powder in the liquid-flow powder slurry is 7 / 3-4 / 1;

[0021] 6) Low-temperature reduction sintering

[0022] The powder collected after spraying is placed into a carbon coating for sintering;

[0023] 7) Screening

[0024] The sintered powder is then placed into a standard vibrating screen for sieving.

[0025] Preferably, in step 3), a ball mill is used for dry grinding and mixing, with the mass ratio of material to grinding balls being 1 / 2 to 1 / 1, and the ball milling time being 0.5h to 1h.

[0026] Further optimization is made in step 4), where the weight ratio of material to grinding balls is 1 / 3 to 1 / 1, and the ball milling time is 1 to 2 hours.

[0027] Further preferred, in step 4), the liquid solvent is water or an organic solvent. When water is used as the liquid solvent, the weight ratio of the liquid powder to the liquid solvent is 1 / 1 to 2 / 1, and the weight ratio of the binder to the liquid powder is 1 / 10 to 3 / 10. When an organic solvent is used as the liquid solvent, the weight ratio of the binder to the liquid powder is 1 / 20 to 3 / 20, and the weight ratio of the liquid powder to the liquid solvent is 1 / 5 to 1 / 1.

[0028] Further preferred, in step 5), the diameter of the airflow nozzle is 1-5mm, the diameter of the liquid flow nozzle is 1-5mm; the airflow pressure is 1-5MPa, the liquid flow pressure is 0.5-2MPa; the distance between the airflow nozzle and the liquid flow nozzle is 0.2-1m, the height difference is 0.5-1m; the distance between the airflow nozzle and the lower collecting device is 0.5-2m, and the lower collecting device collects powder.

[0029] Further optimization is made in step 6), where the sintering temperature is 400-600℃ and the sintering time is 2-5h.

[0030] Further optimization, in step 6), the carbon coating body adopts a graphite mold, which is filled with iron sand.

[0031] Further optimization is made in step 7), where the sieve mesh ranges from 100 to 400 mesh.

[0032] This invention provides nickel-copper-boron nitride powder with uniform composition, high relative density, good flowability, wide particle size range, and typical coating morphology. The powder can be used to prepare wear-resistant coatings, sealing coatings, and lubricating coatings, which can significantly reduce the gap between components and improve the wear resistance, erosion resistance, and thermal stability of the substrate.

[0033] The present invention provides a method for preparing nickel-copper boron nitride powder with the following advantages: Utilizing the characteristics of high-speed gas flow promoting rapid evaporation of the liquid in the fluid method, the coating morphology of the nickel-copper boron nitride powder can be significantly improved, while simultaneously achieving metal phase doping, thereby significantly improving the powder's performance; by controlling the gas phase flow, the metal phase ratio can be precisely controlled and adjusted as needed; the introduction of copper further improves the coating's strength and hardness, and enhances its corrosion resistance and oxidation resistance; the low-temperature reduction sintering process, through carbon reduction at low temperatures, eliminates the need for reducing gas and high-temperature reduction, reducing production costs while ensuring powder purity; commercially available raw materials are used, the process equipment is simple, no protective gas is required, lowering the threshold for industrialization, resulting in low production costs and significantly improved production efficiency, meeting the requirements of mass production. Attached Figure Description

[0034] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments:

[0035] Figure 1 The image shows the microstructure of the nickel-copper boron nitride powder obtained in Example 1.

[0036] Figure 2 for Figure 1 A further magnified microscopic morphology image of medium-nickel copper boron nitride powder;

[0037] Figure 3 This is a compositional analysis diagram of nickel-copper-boron-nitride powder. Detailed Implementation

[0038] The present invention will be further explained below with reference to specific implementation schemes, but this explanation does not limit the scope of the invention.

[0039] This invention addresses the current problems of difficulty in controlling the composition and structure of nickel copper boron nitride powder, expensive production equipment, complex preparation methods, and inability to mass-produce it, and provides an easy-to-implement solution.

[0040] This invention solves the problems of purity, density, and flowability of nickel-copper boron nitride powder through research and development of raw materials, equipment, and processes. It uses conventional equipment to reduce production costs and mass-produces high-performance nickel-copper boron nitride powder, which can be used to prepare coatings such as wear-resistant coatings, sealing coatings, and lubricating coatings.

[0041] This invention provides a nickel-copper boron nitride powder, comprising, by weight: copper: 10-30%, boron nitride: 9-20%, carbon: 0-10%, silicon ≤5%, and the balance being nickel, wherein the loose packing density of the nickel-copper boron nitride powder is 1-2 g / cm³. 3 The fluidity is ≤120s / 50g, and the particle size is between -100 mesh and +400 mesh. The nickel-copper-boron nitride powder component has a dispersed polymer structure.

[0042] This invention also provides a method for preparing nickel-copper boron nitride powder, comprising the following steps:

[0043] 1) Powder selection

[0044] Based on the performance requirements of nickel-copper-boron nitride powder, nickel powder, copper powder, boron nitride powder, and graphite powder of different particle sizes are selected, with large particles serving as the core and small particles as the coating.

[0045] Specifically, nickel powder, copper powder, boron nitride powder, and graphite powder with a purity higher than 99.99% and a particle size in the range of 2-150μm are selected for use.

[0046] 2) Additive selection

[0047] Select binders such as water glass and silica sol, and prepare an aqueous solution with a concentration of 1-5% according to the performance requirements of the product for later use;

[0048] 3) Preparation of airflow powder

[0049] Nickel powder and copper powder are added to a mixer in a weight ratio of 4 / 3 to 7 / 1 and mixed to obtain air-flow powder. The mixing time is 0.5 to 1 hour.

[0050] If necessary, a ball mill can be used for dry grinding and mixing, with the material to grinding balls mass ratio of 1 / 2 to 1 / 1, and the ball milling time of 0.5h to 1h.

[0051] 4) Preparation of liquid-powder slurry

[0052] Graphite powder and boron nitride powder are added to a ball mill at a weight ratio of 0-1 / 1 to mix and obtain liquid powder. The weight ratio of material to grinding balls is 1 / 3-1 / 1, and the ball milling time is 1-2 hours.

[0053] Liquid powder is mixed with liquid solvent and binder to obtain liquid powder slurry. The liquid solvent is water or an organic solvent (alcohol, petroleum ether, etc.). When water is used as the liquid solvent, the weight ratio of liquid powder to liquid solvent is 1 / 1 to 2 / 1, and the weight ratio of binder to liquid powder is 1 / 10 to 3 / 10. When an organic solvent is used as the liquid solvent, the weight ratio of binder to liquid powder is 1 / 20 to 3 / 20, and the weight ratio of liquid powder to liquid solvent is 1 / 5 to 1 / 1.

[0054] 5) Fluid jet mixing

[0055] High-pressure gas is used for the injection of air-jet powder and liquid-jet powder slurry. The weight ratio of air-jet powder to liquid-jet powder in the slurry is 7 / 3-4 / 1. The diameter of the air-jet nozzle is 1-5 mm, and the diameter of the liquid-jet nozzle is 1-5 mm. The air-jet pressure is 1-5 MPa, and the liquid-jet pressure is 0.5-2 MPa. The distance between the air-jet nozzle and the liquid-jet nozzle is 0.2-1 m, and the height difference is 0.5-1 m. The distance between the air-jet nozzle and the lower collection device is 0.5-2 m, and the lower collection device collects the powder.

[0056] 6) Low-temperature reduction sintering

[0057] The powder collected after spraying is placed into a carbon coating for sintering at a temperature of 400-600℃ for 2-5 hours. The carbon coating uses a graphite mold with iron sand inside, which plays a role in reduction and protection during the sintering process.

[0058] 7) Screening

[0059] The sintered powder is placed in a standard vibrating screen for sieving, with the screen mesh ranging from 100 to 400 mesh.

[0060] Example 1

[0061] The preparation method of nickel-copper boron nitride powder includes the following steps:

[0062] 1) Powder selection

[0063] Select powders with a purity higher than 99.99%, with nickel powder having a particle size of approximately 80 μm, copper powder approximately 60 μm, boron nitride powder approximately 90 μm, and graphite powder approximately 100 μm.

[0064] 2) Additive selection

[0065] Water glass was selected as the binder and prepared as a 1% aqueous solution for later use;

[0066] 3) Preparation of airflow powder

[0067] Nickel powder and copper powder were added to a mixer at a weight ratio of 5 / 2 to obtain air-flow powder. The mixing time was 0.5 hours.

[0068] 4) Preparation of liquid-powder slurry

[0069] Graphite powder and boron nitride powder were added to a ball mill at a weight ratio of 1 / 2 to mix and obtain liquid powder. The weight ratio of material to grinding balls was 1 / 1, and the ball milling time was 1 hour.

[0070] The liquid flow powder is mixed with the liquid flow solvent and the binder to obtain the liquid flow powder slurry, wherein the liquid flow solvent is water, the weight ratio of the liquid flow powder to the liquid flow solvent is 2 / 1, and the weight ratio of the binder to the liquid flow powder is 1 / 10.

[0071] 5) Fluid jet mixing

[0072] High-pressure gas is used to jet nickel and copper powder, and to jet boron nitride and graphite powder. The weight ratio of the jet powder to the liquid powder in the jet powder slurry is 7 / 3. The diameter of the jet nozzle is 1 mm, and the diameter of the liquid nozzle is 2 mm. The jet pressure is 1 MPa, and the liquid pressure is 0.5 MPa. The distance between the jet nozzle and the liquid nozzle is 0.2 m, and the height difference is 0.8 m. The distance between the jet nozzle and the lower collection device is 0.5 m, and the lower collection device collects the powder.

[0073] 6) Low-temperature reduction sintering

[0074] The powder collected after spraying is placed into a carbon coating for sintering at a temperature of 400℃ for 4 hours. The carbon coating uses a graphite mold and is filled with iron sand, which plays a role in reduction and protection during the sintering process.

[0075] 7) Screening

[0076] The sintered powder is placed in a standard vibrating sieve for sieving to remove coarse powder above 100 mesh and fine powder below 400 mesh, and the finished powder between 100 and 400 mesh is collected.

[0077] Example 2

[0078] The preparation method of nickel-copper boron nitride powder includes the following steps:

[0079] 1) Powder selection

[0080] Select powders with a purity higher than 99.99%, with nickel powder having a particle size of approximately 50 μm, copper powder approximately 70 μm, and boron nitride powder approximately 100 μm.

[0081] 2) Additive selection

[0082] Water glass was selected as the binder and prepared as a 3% aqueous solution for later use;

[0083] 3) Preparation of airflow powder

[0084] Nickel powder and copper powder were added to a mixer at a weight ratio of 11 / 5 to obtain airflow powder. The mixing time was 1 hour.

[0085] 4) Preparation of liquid-powder slurry

[0086] Boron nitride powder was added to a ball mill to obtain liquid powder, wherein the weight ratio of material to grinding balls was 1 / 3, and the ball milling time was 1 hour.

[0087] The liquid flow powder is mixed with the liquid flow solvent and the binder to obtain a liquid flow powder slurry, wherein the liquid flow solvent is alcohol, the weight ratio of the binder to the liquid flow powder is 1 / 20, and the weight ratio of the liquid flow powder to the liquid flow solvent is 1 / 1.

[0088] 5) Fluid jet mixing

[0089] High-pressure gas is used to jet nickel and copper powder, and to jet boron nitride powder using liquid jet. The weight ratio of the jet powder to the liquid powder slurry is 4 / 1. The diameter of the jet nozzle is 2 mm, and the diameter of the liquid nozzle is 1 mm. The gas pressure is 2 MPa, and the liquid pressure is 0.5 MPa. The distance between the jet nozzle and the liquid nozzle is 0.6 m, and the height difference is 0.6 m. The distance between the jet nozzle and the lower collection device is 1 m, and the lower collection device collects the powder.

[0090] 6) Low-temperature reduction sintering

[0091] The powder collected after spraying is placed into a carbon coating for sintering at a temperature of 500℃ for 4 hours. The carbon coating is made of graphite mold and contains iron sand, which plays a role in reduction and protection during the sintering process.

[0092] 7) Screening

[0093] The sintered powder is placed in a standard vibrating sieve for sieving to remove coarse powder above 140 mesh and fine powder below 360 mesh, and the finished powder between 140 and 360 mesh is collected.

[0094] Example 3

[0095] The preparation method of nickel-copper boron nitride powder includes the following steps:

[0096] 1) Powder selection

[0097] Select powders with a purity higher than 99.99%, with nickel powder having a particle size of approximately 50 μm, copper powder approximately 60 μm, boron nitride powder approximately 15 μm, and graphite powder approximately 30 μm.

[0098] 2) Additive selection

[0099] Silica sol was selected as the binder and prepared as a 2% aqueous solution for later use;

[0100] 3) Preparation of airflow powder

[0101] Nickel powder and copper powder were added to a ball mill at a weight ratio of 4 / 3 to obtain air-flow powder. The ratio of material to grinding balls was 1 / 2, and the mixing time was 0.5 hours.

[0102] 4) Preparation of liquid-powder slurry

[0103] Graphite powder and boron nitride powder were added to a ball mill at a weight ratio of 1 / 2 to obtain liquid powder. The weight ratio of material to grinding balls was 1 / 3, and the ball milling time was 2 hours.

[0104] The liquid flow powder is mixed with a liquid flow solvent and a binder to obtain a liquid flow powder slurry, wherein the liquid flow solvent is petroleum ether, the weight ratio of the binder to the liquid flow powder is 3 / 20, and the weight ratio of the liquid flow powder to the liquid flow solvent is 1 / 5.

[0105] 5) Fluid jet mixing

[0106] High-pressure gas is used to jet nickel powder and copper powder, and to jet boron nitride and graphite powder using liquid jet. The weight ratio of the air jet powder to the liquid jet powder slurry is 7 / 3. The diameter of the air jet nozzle is 5 mm, and the diameter of the liquid jet nozzle is 3 mm. The air jet pressure is 5 MPa, and the liquid jet pressure is 1.5 MPa. The distance between the air jet nozzle and the liquid jet nozzle is 1 m, and the height difference is 0.6 m. The distance between the air jet nozzle and the lower collection device is 1 m, and the lower collection device collects the powder.

[0107] 6) Low-temperature reduction sintering

[0108] The powder collected after spraying is placed into a carbon coating for sintering at a temperature of 450℃ for 5 hours. The carbon coating is made of graphite mold and filled with iron sand, which plays a role in reduction and protection during the sintering process.

[0109] 7) Screening

[0110] The dry powder obtained after sintering is placed in a standard vibrating sieve for sieving to remove coarse powder above 160 mesh and fine powder below 320 mesh, and the finished powder between 160 and 320 mesh is collected.

[0111] Example 4

[0112] The preparation method of nickel-copper boron nitride powder includes the following steps:

[0113] 1) Powder selection

[0114] Select powders with a purity higher than 99.99%, with nickel powder particle size of approximately 100 μm, copper powder particle size of approximately 120 μm, boron nitride powder particle size of approximately 5 μm, and graphite powder particle size of approximately 20 μm;

[0115] 2) Additive selection

[0116] Silica sol was selected as the binder and prepared into a 4% aqueous solution according to the performance requirements of the product.

[0117] 3) Preparation of airflow powder

[0118] Nickel powder and copper powder were added to a ball mill at a weight ratio of 3:1 to obtain airflow powder. The mass ratio of material to grinding balls was 1:1, and the mixing time was 1 hour.

[0119] 4) Preparation of liquid-powder slurry

[0120] Graphite powder and boron nitride powder were added to a ball mill at a weight ratio of 2 / 3 to obtain liquid powder. The weight ratio of material to grinding balls was 1 / 1, and the ball milling time was 2 hours.

[0121] The liquid flow powder is mixed with the liquid flow solvent and the binder to obtain the liquid flow powder slurry, wherein the liquid flow solvent is alcohol, the weight ratio of the binder to the liquid flow powder is 1 / 10, and the weight ratio of the liquid flow powder to the liquid flow solvent is 1 / 2.

[0122] 5) Fluid jet mixing

[0123] High-pressure gas is used to jet nickel powder and copper powder, and to jet boron nitride and graphite powder using liquid jet. The weight ratio of the air jet powder to the liquid jet powder slurry is 4 / 1. The diameter of the air jet nozzle is 4 mm, and the diameter of the liquid jet nozzle is 2 mm. The air jet pressure is 3 MPa, and the liquid jet pressure is 1 MPa. The distance between the air jet nozzle and the liquid jet nozzle is 0.8 m, and the height difference is 0.5 m. The distance between the air jet nozzle and the lower collection device is 2 m, and the lower collection device collects the powder.

[0124] 6) Low-temperature reduction sintering

[0125] The powder collected after spraying is placed into a carbon coating for sintering at a temperature of 550℃ for 3 hours. The carbon coating uses a graphite mold and is filled with iron sand, which plays a role in reduction and protection during the sintering process.

[0126] 7) Screening

[0127] The dry powder obtained after sintering is placed in a standard vibrating sieve for sieving to remove coarse powder above 100 mesh and fine powder below 400 mesh, and collect finished powder between 100 and 400 mesh.

[0128] Example 5

[0129] The preparation method of nickel-copper boron nitride powder includes the following steps:

[0130] 1) Powder selection

[0131] Select powders with a purity higher than 99.99%, with nickel powder having a particle size of approximately 120 μm, copper powder approximately 150 μm, boron nitride powder approximately 2 μm, and graphite powder approximately 10 μm.

[0132] 2) Additive selection

[0133] Water glass was selected as the binder and prepared as a 5% aqueous solution for later use;

[0134] 3) Preparation of airflow powder

[0135] Nickel powder and copper powder were added to a ball mill at a weight ratio of 7:1 to obtain airflow powder. The mass ratio of material to grinding balls was 1:2, and the mixing time was 1 hour.

[0136] 4) Preparation of liquid-powder slurry

[0137] Graphite powder and boron nitride powder were added to a ball mill at a weight ratio of 1:1 to obtain liquid powder. The weight ratio of material to grinding balls was 1:3, and the ball milling time was 2 hours.

[0138] The liquid flow powder is mixed with the liquid flow solvent and the binder to obtain the liquid flow powder slurry, wherein the liquid flow solvent is water, the weight ratio of the liquid flow powder to the liquid flow solvent is 1 / 1, and the weight ratio of the binder to the liquid flow powder is 3 / 10.

[0139] 5) Fluid jet mixing

[0140] High-pressure gas is used to jet nickel powder and copper powder, and to jet boron nitride and graphite powder using liquid jet. The weight ratio of the air jet powder to the liquid jet powder slurry is 4 / 1. The diameter of the air jet nozzle is 4 mm, and the diameter of the liquid jet nozzle is 5 mm. The air jet pressure is 3 MPa, and the liquid jet pressure is 2 MPa. The distance between the air jet nozzle and the liquid jet nozzle is 0.4 m, and the height difference is 1 m. The distance between the air jet nozzle and the lower collection device is 1.5 m, and the lower collection device collects the powder.

[0141] 6) Low-temperature reduction sintering

[0142] The powder collected after spraying is placed into a carbon coating for sintering at a temperature of 600℃ for 2 hours. The carbon coating is made of graphite mold and contains iron sand, which plays a role in reduction and protection during the sintering process.

[0143] 7) Screening

[0144] The dry powder obtained after sintering is placed in a standard vibrating sieve for sieving to remove coarse powder above 140 mesh and fine powder below 360 mesh, and collect the finished powder between 140 and 360 mesh.

[0145] The above method can be used to prepare nickel-copper boron nitride powder with a copper content of 10-30 wt.%, a boron nitride content of 9-20 wt.%, a carbon content of 0-10 wt.%, a silicon content ≤5 wt.%, and the balance being nickel. The loose packing density of the powder is 1-2 g / cm³. 3 The flowability is ≤120s / 50g, the particle size is between (-100 mesh) and (+400 mesh), and the nickel-copper-boron nitride powder components exhibit a dispersed polymer structure (e.g., Figure 1 , Figure 2 As shown in Table 1, the powder properties are as follows: Figure 3 .

[0146] Table 1: Powder Properties

[0147]

[0148]

[0149] The embodiments of the present invention have been described in detail above with reference to the accompanying drawings. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention.

Claims

1. Nickel-copper boron nitride powder, characterized in that, By weight, it comprises the following components: copper: 10-30%, boron nitride: 9-20%, carbon: 0-10%, silicon ≤5%, and the balance being nickel, wherein the loose packing density of the nickel-copper-boron nitride powder is 1-2 g / cm³. 3 The fluidity is ≤120s / 50g, and the particle size is between -100 mesh and +400 mesh. The nickel-copper-boron nitride powder component has a dispersed polymer structure. The preparation method of the nickel-copper boron nitride powder includes the following steps: 1) Powder selection Select nickel powder, copper powder, boron nitride powder, and graphite powder with a purity higher than 99.99%, and the powder particle size is in the range of 2-150μm; 2) Additive selection Water glass or silica sol is selected as the binder and prepared as an aqueous solution with a concentration of 1-5%; 3) Preparation of airflow powder Nickel powder and copper powder are added to a mixer in a weight ratio of 4 / 3 to 7 / 1 and mixed to obtain airflow powder. 4) Preparation of liquid-powder slurry Graphite powder and boron nitride powder were added to a ball mill at a weight ratio of 0-1 / 1 and mixed to obtain liquid flow powder. The liquid flow powder is mixed with a liquid flow solvent and a binder to obtain a liquid flow powder slurry, wherein the liquid flow solvent is water or an organic solvent; 5) Fluid jet mixing High-pressure gas is used to spray air-flow powder and liquid-flow powder slurry, wherein the weight ratio of air-flow powder to liquid-flow powder in the liquid-flow powder slurry is 7 / 3-4 / 1, wherein the air-flow pressure is 1-5 MPa and the liquid-flow pressure is 0.5-2 MPa; 6) Low-temperature reduction sintering The powder collected after spraying is placed into a carbon coating for sintering, wherein the sintering temperature is 400-600℃; 7) Screening The sintered powder is then placed into a standard vibrating screen for sieving.

2. The nickel-copper boron nitride powder according to claim 1, characterized in that: In step 3), a ball mill is used for dry grinding and mixing, with the mass ratio of material to grinding balls being 1 / 2 to 1 / 1, and the ball milling time being 0.5h to 1h.

3. The nickel-copper boron nitride powder according to claim 1, characterized in that: In step 4), the weight ratio of material to grinding balls is 1 / 3 to 1 / 1, and the grinding time is 1 hour to 2 hours.

4. The nickel-copper boron nitride powder according to claim 1, characterized in that: In step 4), the liquid solvent is water or an organic solvent. When water is used as the liquid solvent, the weight ratio of liquid powder to liquid solvent is 1 / 1 to 2 / 1, and the weight ratio of binder to liquid powder is 1 / 10 to 3 / 10. When an organic solvent is used as the liquid solvent, the weight ratio of binder to liquid powder is 1 / 20 to 3 / 20, and the weight ratio of liquid powder to liquid solvent is 1 / 5 to 1 / 1.

5. The nickel-copper boron nitride powder according to claim 1, characterized in that: In step 5), the diameter of the airflow nozzle is 1-5mm, the diameter of the liquid flow nozzle is 1-5mm, the distance between the airflow nozzle and the liquid flow nozzle is 0.2-1m, the height difference is 0.5-1m, the distance between the airflow nozzle and the lower collection device is 0.5-2m, and the lower collection device collects the powder.

6. The nickel-copper boron nitride powder according to claim 1, characterized in that: In step 6), the sintering time is 2-5 hours.

7. The nickel-copper boron nitride powder according to claim 1, characterized in that: In step 6), the carbon coating is made using a graphite mold, which is filled with iron sand.

8. The nickel-copper boron nitride powder according to claim 1, characterized in that: In step 7), the sieve mesh ranges from 100 to 400 mesh.

Citation Information

Patent Citations

  • Wearable composite powder for sealing, coating and preparation methods

    CN102168239A

  • METHOD FOR MANUFACTURING ZnO VAPOR DEPOSITION MATERIAL

    JP2010185132A